Kualitas Air dan Sumbangan Hara dari Air Irigasi Sidorejo - Jaka Suyono; Sutopo Sutopo; Herry Widijanto (Universitas Sebelas Maret, 2007)
Irrigation water contributes several kind of nutrients to lowland rice and sometimes creates some problems. Research on irrigation water connected with fertilizers requirement and its effect on plant growth and crop yield was still limited. Water samples from Sidorejo irrigation in Central Java, at dry season in 2001, analyzed in laboratory its anion, cation, and water quality. The result showed that water quality from Sidorejo irrigation is suitable and did not give any unfavorable effect on the growth and yield of rice plant; which the values of SAR is very good, DHL and TDS were good-very good, Cl- is very good, percentage Na+ is moderate-good, SO4- is very good, and pH is normal. Irrigation water from Sidorejo irrigation were could supply 4,62 kg N/ha/season, 0,02 kg P/ha/season, 8,45 kg K/ha/season, 48,36 kg S/ha/season, 128,26 kg Ca/ha/season, and 34,89 kg Mg/ha/season respectively. The amount of nutrients supply have to be considered in the decision of fertilizer need